Improving Communication Managerial Skill Among Women: Study On PT XYZ - Azka Mohammad; Harliantara, Harliantara; Nur’annafi Farni Syam Maella; Zulaikha, Zulaikha (Jurnal Ekonomi, 2024)
This case study explores the communication styles and managerial skills of women leaders at PT XYZ, a prominent Indonesian company. The research seeks to uncover the distinct strengths that women bring to management positions and invesorganizational empower and bolster their growth as leaders. Previous research has emphasized the positive communication skills that women frequently demonstrate in professional settings, including their ability to empathize, pay attention to details, and make inclusive decisions. The "Women's Management Model" proposes that these characteristics can be valuable assets in management positions. Nevertheless, women leaders may encounter cultural biases that associate assertiveness and authority with more "masculine" traits. The case study methodology, as described by Robert K. Yin, was used to thoroughly examine women managers at PT XYZ. The research team analyzed propositions and conducted tests using the collected evidence to gain a thorough understanding of the phenomenon. The findings suggest that women managers at PT XYZ possess excellent communication skills, which encompass active listening, conflict resolution, and team-building. These strengths greatly enhance employee engagement and productivity. Nevertheless, the women also encounter difficulties in being seen as authoritative figures, as their communication styles are occasionally seen as too "soft" or "emotional" for leadership positions. In order to fully unleash the capabilities of women leaders, it is crucial for organizations to foster inclusive environments that recognize and appreciate the distinct communication strengths possessed by female managers. Implementing mentorship programs, leadership development initiatives, and inclusive policies can be instrumental in empowering women and cultivating a culture of collaboration and effectiveness within teams.